Chimeric antigen receptor with novel intracellular modules improves antitumor performance of T cells - Pengju Wang; Yiyi Wang; Xiaojuan Zhao; Rui Zheng; Yiting Zhang; Ruotong Meng; Hao Dong; Sixin Liang; Xinyi He; Yang Song; Haichuan Su; Bo Yan; et al. (Signal Transduction and Targeted Therapy)
Abstract The excessive cytokine release and limited persistence represent major challenges for chimeric antigen receptor T (CAR-T) cell therapy in diverse tumors. Conventional CARs employ an intracellular domain (ICD) from the ζ subunit of CD3 as a signaling module, and it is largely unknown how alternative CD3 chains potentially contribute to CAR design. Here, we obtained a series of CAR-T cells against HER2 and mesothelin using a domain comprising a single immunoreceptor tyrosine-based activation motif from different CD3 subunits as the ICD of CARs. While these reconstituted CARs conferred sufficient antigen-specific cytolytic activity on equipped T cells, they elicited low tonic signal, ameliorated the exhaustion and promoted memory differentiation of these cells. Intriguingly, the CD3ε-derived ICD outperformed others in generation of CAR-T cells that produced minimized cytokines. Mechanistically, CD3ε-based CARs displayed a restrained cytomembrane expression on engineered T cells, which was ascribed to endoplasmic reticulum retention mediated by the carboxyl terminal basic residues. The present study demonstrated the applicability of CAR reconstitution using signaling modules from different CD3 subunits, and depicted a novel pattern of CAR expression that reduces cytokine release, thus paving a way for preparation of CAR-T cells displaying improved safety and persistence against diverse tumor antigens.